Parents' Responsibilities for Children's Education in Islam Reviewed from Q.S. At Tahrim Verse 6: A Study of Ibn Kathir's Interpretation - Miftahur Rahmi; Rosdialena (Journal Of Psychology, Counseling And Education, 2026)
This study aims to examine the responsibility of parents towards children's education in Islam based on QS. At-Tahrim verse 6 through the perspective of Tafsir Ibn Kathir. This study uses a qualitative approach with library research methods. Primary data were obtained from the Qur'an and Tafsir Ibn Katsir, while secondary data came from books, journals, and related research. The results of the study indicate that QS. At-Tahrim verse 6 contains an order for parents to protect their families through education based on Islamic teachings. This responsibility includes education in faith, worship, morals, social, as well as supervision and protection of children. In addition, the values ​​contained in the verse remain relevant in facing the challenges of children's education in the modern era. Therefore, the family is the main foundation in forming a generation that is faithful, has noble morals, and is able to face the development of the times wisely.